Blocked Atrial Bi/Trigeminy In Utero Evolving in Supraventricular Tachycardia after Birth. (16th July 2012) - Martucci, V.; Cerekja, A.; Caiaro, A.; Bosco, G.; Lucchini, R.; Piacentini, G.; Marino, B.; Ventriglia, Flavia
Abstract : Transient episodes of fetal bradycardia (heart rate less than 110 bpm) are usually benign and typically result from increased vagal stimulation in the fetus. Causes of sustained fetal bradycardia include sinus bradycardia, blocked atrial bigeminy/trigeminy, high-degree atrioventricular block, and long QT syndrome. We present the case of a 34-year-old Caucasian patient referred to our department for "blocked atrial bigeminy with pseudobradycardia" detected elsewhere at 33 weeks of gestation. A fetal echocardiography showed during all the examination a blocked atrial trigeminy with a mean fetal heart rate of 100 bpm. After birth three subsequent ECGs until day 3 showed no evidence of atrial extrasystoles, confirming the well-known frequent regression of this kind of fetal benign arrhythmia, but on day 11 recurrence of supraventricular trigeminy and development of episodes of paroxystic supraventricular tachycardia were observed. On the basis of this observation, we recommend that fetuses with complex atrial ectopic beats should be closely monitored before and after birth for evidence of new arrhythmias.